2021
DOI: 10.17245/jdapm.2021.21.5.441
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of pre-operative medication with paracetamol and ketorolac on the success of inferior alveolar nerve block in patients with symptomatic irreversible pulpitis: a double-blind randomized clinical trial

Abstract: Background The efficacy of local anesthesia decreases in patients with symptomatic irreversible pulpitis. Therefore, it was proposed that the use of premedication with an anti-inflammatory drug might increase the success rate of pulpal anesthesia in mandibular posterior teeth with vital inflamed pulp. Methods One hundred thirty-four patients who were actively experiencing pain willingly participated in this study. The Heft Parker (HP) visual analog scale (VAS) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…15 Ketorolac has shown promising results in most studies, however Kumar et al reported statistically insignificant difference in pain improvement threshold between prophylactic ketorolac and paracetamol on the success of IANB. 32 A systematic review by Sivaramakrishnan et al included four studies to evaluate the success of IANB in conjunction with ketorolac as compared to other NSAIDs and placebo. The authors concluded that oral premedication with ketorolac should be considered before initiation of endodontic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Ketorolac has shown promising results in most studies, however Kumar et al reported statistically insignificant difference in pain improvement threshold between prophylactic ketorolac and paracetamol on the success of IANB. 32 A systematic review by Sivaramakrishnan et al included four studies to evaluate the success of IANB in conjunction with ketorolac as compared to other NSAIDs and placebo. The authors concluded that oral premedication with ketorolac should be considered before initiation of endodontic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…15 Ketorolac has shown promising results in most studies, however Kumar et al reported statistically insignificant difference in pain improvement threshold between prophylactic ketorolac and paracetamol on the success of IANB. 32…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned article [ 1 ] was published in the Journal of Dental Anesthesia and Pain Medicine with the clinical trial registration number missing. The correct clinical trial registration number in Notes is written bellow:…”
mentioning
confidence: 99%